Effects of the expression of the bacterial YEFM-YOEBSPN chromosomal toxin-antitoxin system in Arabidopsis Thaliana / Fauziah Abu Bakar - Fauziah, Abu Bakar (2016)

(untitled)
Toxin-antitoxin (TA) systems are extensively found in bacteria as well as in archaea where they play diverse roles in important cellular functions. Bacterial TA systems usually comprise of a pair of genes encoding a stable toxin and its cognate labile antitoxin and are located in the chromosome or in plasmids. Chromosomally-encoded TA systems are involved in a variety of cellular processes including as part of the global stress response of bacteria, and as mediators of programmed cell death as well as biofilm formation, in which the activation of the toxins usually leads to cell death or dormancy. The genome of the human pathogen Streptococcus pneumoniae contains up to 10 putative TA systems and among these, the yefM-yoeBSpn locus has been well studied and demonstrated to be biologically functional. Overexpression of the yoeBSpn toxin has been shown to lead to cell stasis and eventually cell death in its native host cell as well as in E. coli. Several toxins of TA systems have been heterologously expressed in eukaryotic systems including yeasts, zebrafish, frog embryos and human cell lines where they have been shown to be lethal. However, there has been no report on the functionality of any bacterial TA systems in plants. In this study, a two-component 17-β-estradiol-inducible expression system was utilized to investigate the heterologous expression of the yoeBSpn toxin along with its cognate yefMSpn antitoxin in Arabidopsis thaliana. The coding sequence of the yoeBSpn toxin was cloned as a translational fusion with Green Fluorescent Protein and A. thaliana was transformed via floral dip using Agrobacterium tumefaciensmediated transformation method. Transgenic A. thaliana were allowed to grow on selection media until T2 generation. Induced expression of the yoeBSpn toxin-GFP fusion transgene apparently triggered apoptosis and was lethal in A. thaliana. To investigate if expression of the yefMSpn could mitigate the toxicity of yoeBSpn in A. thaliana, transgenic plant carrying yefMSpn was first constructed and then cross-pollinated with transgenic plant containing the yoeBSpn-GFP transgene. The yefMSpn × yoeBSpn-GFP hybrid transgenic plants obtained were allowed to grow until maturity on selection media. When co-expressed in A. thaliana, the YefMSpn antitoxin was found to neutralize the toxicity of YoeBSpn-GFP. Interestingly, the inducible expression of both the yefMSpn antitoxin and yoeBSpn toxin-GFP fusion transgenes in transgenic hybrid plants resulted in larger rosette leaves, taller plants with more inflorescence stems and increased silique production. The detailed mechanism by which co-expression of yoeBSpn-GFP and yefMSpn led to enhanced plant growth remains to be elucidated. In their original bacterial hosts, YefMSpn forms a tight protein complex with YoeBSpn and this TA complex binds to the operator site overlapping the yefM-yoeBSpn promoter to repress its transcription. It is possible that the YefM-YoeBSpn complex in A. thaliana binds to certain regions of the plant genome leading to the enhanced growth phenotype. To our knowledge, this is the first demonstration of a prokaryotic antitoxin neutralizing its cognate toxin in plant cells. The functional lethality of the YoeBSpn toxin enables it to be harnessed for a potential novel plant cell ablation system.